2018
DOI: 10.7554/elife.32808
|View full text |Cite
|
Sign up to set email alerts
|

Developmental evolution of the forebrain in cavefish, from natural variations in neuropeptides to behavior

Abstract: The fish Astyanax mexicanus comes in two forms: the normal surface-dwelling and the blind depigmented cave-adapted morphs. Comparing the development of their basal forebrain, we found quantitative differences in numbers of cells in specific clusters for six out of nine studied neuropeptidergic cell types. Investigating the origins of these differences, we showed that early Shh and Fgf signaling impact on the development of NPY and Hypocretin clusters, via effect on Lhx7 and Lhx9 transcription factors, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 82 publications
7
46
0
Order By: Relevance
“…To determine if there are changes in the size of brain regions that may be associated with evolved behavioral differences, we quantified 13 additional brain regions, including the tectum, cerebellum, pallium, and four regions of the hypothalamus (Fig 1F–K and Table S1, Fig S4, Movie S1, and Movie S2) in accordance with previously described nomenclature [7]. Consistent with previous reports, the optic tectum and neuropil were reduced, and the total hypothalamus volume was enlarged in all three cavefish populations [15,41,42]. The increase in hypothalamus volume was due to an enlargement of rostral and intermediate zones of the hypothalamus, with no differences between surface fish and cavefish populations in the volume of the diffuse nucleus of the hypothalamus (Fig 1K, Fig S4).…”
Section: Resultssupporting
confidence: 77%
“…To determine if there are changes in the size of brain regions that may be associated with evolved behavioral differences, we quantified 13 additional brain regions, including the tectum, cerebellum, pallium, and four regions of the hypothalamus (Fig 1F–K and Table S1, Fig S4, Movie S1, and Movie S2) in accordance with previously described nomenclature [7]. Consistent with previous reports, the optic tectum and neuropil were reduced, and the total hypothalamus volume was enlarged in all three cavefish populations [15,41,42]. The increase in hypothalamus volume was due to an enlargement of rostral and intermediate zones of the hypothalamus, with no differences between surface fish and cavefish populations in the volume of the diffuse nucleus of the hypothalamus (Fig 1K, Fig S4).…”
Section: Resultssupporting
confidence: 77%
“…A recently published neuroanatomical brain atlas in cavefish shows that various subnuclei within the hypothalamus are morphometrically different (Loomis et al, 2019). Similarly, these data have revealed that the forebrain, an area which contains cell populations that are similar to the mammalian amygdala and hippocampus, is significantly expanded in cavefish populations (Alié et al, 2018;Loomis et al, 2019). These data suggest that areas that are essential to the proper modulation of stress are evolutionarily different between cave and epigean Astyanax.…”
Section: Neuroanatomical Regions That Modulate Stress May Be Differenmentioning
confidence: 79%
“…Stress is modulated by myriad neuroanatomical loci, including the hypothalamus, the amygdala, hippocampus, preoptic area of the hypothalamus, and habenulae (Tovote et al, 2015), and many of these regions have been shown to differ significantly between cave and surface morphs in neural activity and/or neuroanatomy (Menuet et al, 2007;Alié et al, 2018;Jaggard et al, 2018;Loomis et al, 2019). For example, in fish and mammals, the hypothalamus has a critical role in the modulation and induction of stress (Spiess et al, 1981;Callahan et al, 1992;Cachat et al, 2010;Steenbergen et al, 2012;Wamsteeker Cusulin et al, 2013;Yeh et al, 2013).…”
Section: Neuroanatomical Regions That Modulate Stress May Be Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mexican tetra Astyanax mexicanus is a versatile model system, which is well suited for the study of the evolution of morphology, behavior, and physiology . The different ecologies of the river and cave habitats of this species have led to the evolution of river dwelling and cave adapted populations which differ in a large number of traits (Figure A,B).…”
Section: Introductionmentioning
confidence: 99%